Avaliação da eficiência de barreiras geoquímicas utilizando HDL no tratamento de drenagem ácida de mina sintética - FERREIRA, Lívia Beatriz Oliveira (2018)
Acid mine drainage (DAM) is one of the major environmental problems caused by the mining activity of coal and sulfide ore. Its formation occurs when large amounts of rocks and / or earth containing sulfides are exposed to the surface. These rocks react with water and air forming acid drainage, this reaction can be accelerated with the presence of bacteria. After the generation of DAM, the formed fluid penetrates the soil and can contaminate groundwater and surface water, soil and vegetation. Due to this several researches are developed aimed at the treatment of AMD, using several techniques. One of these is the neutralization and precipitation, which consists in raising the pH of the DAM so that neutralization occurs, thus precipitating the heavy metals. In this context, this work proposes the use of limestone and synthetic hydrotalcite in the neutralization of AMD. Besides adsorption of sulfate by hydrotalcite. The work consisted of the preparation of the synthetic DAM and the synthesis of hydrotalcite (coprecipitation) for subsequent treatment of AMD. The first experiment was carried out to analyze which Limestone / DAM ratio is most efficient in the neutralization of synthetic DAM. The second experiment had the objective of evaluating the adsorption and neutralization of synthetic DAM. This experiment was carried out in two stages: in the first stage different volumes of synthetic DAM and 0.5 g of calcined hydrotalcite were used at 500 ºC for 2 hours and Second stage experiment used different volumes of AMD and 1 g of limestone and 0.5 g of calcined hydrotalcite at 500 ºC for 2 hours. The parameters used to verify the efficiency of the geochemical barrier were pH, Electrical Conductivity, ICP MS-Quadrupole, Total Iron by Spectrophotometry, Atomic Absorption Spectrometry and Chromatography, as well as the precipitates were analyzed by X-ray Diffraction and Scanning Electron Microscopy. In relation to the neutralization experiment, the Limestone / DAM ratio of 1 g / 100 mL was the most efficient, reaching levels above the minimum allowed limit (LMP) in the first hour of treatment. This limestone/DAM ratio was also efficient in the reduction of electrical conductivity. The adsorption and neutralization tests with HDL and HDL + limestone also showed positive influence on pH and electrical conductivity values. The pH of the treated samples reached values above the minimum permitted limit (LMP) established by resolution 430/2011 of CONAMA for effluents. The adsorption and neutralization processes were efficient in the removal of the heavy metals that constituted the synthetic DAM. For the concentrations of Cu, Cr, Fe, Ni and Zn, there was a reduction of 100%. Mn did not change concentration. The SO42- anion was totally removed in the experiment with HDL at 25 and 55 mL volumes and using HDL + limestone in the 25 mL xi volume. It is noteworthy that in the adsorption and neutralization experiment HDL presented better results in the treatment of AMD than when mixed with limestone.